Analysis of Acceleration of Final Assignment Students of the Basic Education Master Program - Stefani Nawati Ekoresti; Muhamad Komarudin; Enang Rusyana; Euis Susilowati; Arina Rubyasih (Jurnal Studi Guru dan Pembelajaran, 2023)
This study aims to determine the study progress of students of the Master's Program in Basic Education, at Bogor Open University. The problem in this study is to review the length of the study period taken by students, especially in working on the Master's Program Final Project (TAPM) or thesis. The method in this study uses a descriptive survey method to analyze student progress and the length of time needed by students from receiving the supervisor's decree to the BTR 1 stage, from the BTR 1 stage to the BTR 2 stage, and from the BTR 2 stage to the trial exam stage. This research will find out the length of study period needed by students in working on the final project of the master program (TAPM) or thesis. The results of this study are useful as policy proposals for accelerating student studies in the form of curriculum development, academic guidance assistance, and the determination of appropriate supervisors